Efficacy of Lactulose versus Senna Plus Ispaghula Husk Among Patients with Pre-Dialysis Chronic Kidney Disease and Constipation: A Randomized Controlled Trial - Nata, Naowanit; Suebsiripong, Supaporn; Satirapoj, Bancha; Supasyndh, Ouppatham; Chaiprasert, Amnart (International journal of nephrology and renovascular disease, 2021)
Background: Constipation is a common problem among patients with advanced chronic kidney disease (CKD), leading to a loss of quality of life. Pharmacologic treatments are in common use, but whether lactulose and senna plus ispaghula husk is effecive to treat constipation among patients with pre-dialysis CKD remains unknown. Objective: The aim of the study was to compare efficacy of lactulose and senna plus ispaghula husk to treat constipation among patients with pre-dialysis CKD. Methods: A study was conducted among patients with pre-dialysis CKD receiving a diagnosis of constipation by ROME IV criteria. All subjects were randomly assigned to receive either lactulose or senna plus ispaghula husk daily for 14 days. After a 7-day washout period, the patients were switched to the other substance for another 14 days. Primary outcome was complete spontaneous bowel movement (CSBM) weekly, assessed using a stool diary after each laxative. Secondary outcome measure was the change of stool appearance using the Bristol stool form scale (BSFS). Results: A total of 22 patients underwent randomization. Baseline CSBM and BSFS were 3.4 [+ or -] 1.4 and 2.3 [+ or -]1.2 time/week, respectively. At the end of the study, the mean CSBM weekly increased in the lactulose group (mean difference 1.3 [+ or -] 1.6, P < 0.001) and the senna plus ispaghula husk group (mean difference 2.1 [+ or -] 2.1, P < 0.001) from baseline. Comparing CSBM between lactulose and senna plus ispaghula husk exhibited no significant difference (95% CI -1.2 to 0.06; P = 0.276). BSFS was significantly changed after using ispaghula husk with senna, the mean [+ or -] SD of BSFS changed to 1.7 [+ or -] 1.8 (p = 0.001) and after use lactulose, the mean [+ or -] SD of BSFS changed to 1.6 [+ or -] 1.8 (p = 0.001). No significant BSFS change was observed between groups regarding stool appearance. No serious adverse event in either group was found. Conclusion: Lactulose and senna plus ispaghula husk were similar in efficacy to treat constipation among patients with pre-dialysis CKD. Trial Registration: Thai Clinical Trials number is TCTR20200818006. Retrospectively Registered 18 August 2020. Keywords: chronic kidney disease, lactulose, ispaghula husk, senna, constipation